2020
DOI: 10.1159/000509779
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Chain Irradiation in Left-Sided Breast Cancer: Can We Reduce the Risk of Secondary Cancer and Ischaemic Heart Disease with Modern Intensity-Modulated Radiotherapy Techniques?

Abstract: <b><i>Introduction:</i></b> The aim of the present study was to estimate the impact of the addition of internal mammary chain (IMC) irradiation in node-positive left-sided breast cancer (BC) patients undergoing regional nodal irradiation (RNI) and comparatively evaluate excess relative and absolute risks of radiation-induced lung cancer/BC and ischaemic heart disease for intensity-modulated radiotherapy (IMRT) versus 3D conformal radiotherapy (3D-CRT). <b><i>Methods:</i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Intensity Modulated RT (IMRT) represents an advanced form of 3D-Conformal RT that alters the intensity of multiple photon beams and delivers them from diverse directions, creating highly conformal dose distributions [33,79]. With regard to the literature, IMRT achieves the administration of lower doses to a greater proportion of cardiac tissue, thus resulting in an improved sparing of the OARs, dose uniformity, and the coverage of the target volume in comparison to3D-CRT [80].Studies have illustrated that the irradiation of the internal mammary chain (IMC) in left-sided BC patients increases the cardiac dose [81].…”
Section: Intensity Modulated Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Intensity Modulated RT (IMRT) represents an advanced form of 3D-Conformal RT that alters the intensity of multiple photon beams and delivers them from diverse directions, creating highly conformal dose distributions [33,79]. With regard to the literature, IMRT achieves the administration of lower doses to a greater proportion of cardiac tissue, thus resulting in an improved sparing of the OARs, dose uniformity, and the coverage of the target volume in comparison to3D-CRT [80].Studies have illustrated that the irradiation of the internal mammary chain (IMC) in left-sided BC patients increases the cardiac dose [81].…”
Section: Intensity Modulated Radiotherapymentioning
confidence: 99%
“…Studies have shown that VMAT is beneficial for left-sided BC patients by administering lower doses to healthy tissues, including the heart and coronary arteries, and avoiding the induced cardiac dysfunction [36]. In 2021,Zhang et al enrolled 30 patients undergoing RT after a mastectomy [81].Compared to IMRT, VMAT treatment plans resulted in better target volume coverage and reduced heart tissue exposure to radiation.…”
Section: Volumetric Modulated Arc Therapymentioning
confidence: 99%
“…[8][9][10] The role of radiation therapy in subsequent cancer development has been studied for a range of primary cancers, including those of the prostate and rectum, 11 head and neck, 12 and breast. 13 Much of the literature focuses on secondary lung cancer or cardiovascular disease risk after breast cancer radiation therapy. 13,14 Yet less is known about the long-term overall risk of subsequent nonkeratinocyte skin cancers after breast cancer radiation therapy or other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The role of radiation therapy in subsequent cancer development has been studied for a range of primary cancers, including those of the prostate and rectum, head and neck, and breast . Much of the literature focuses on secondary lung cancer or cardiovascular disease risk after breast cancer radiation therapy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation